Pengaruh Pendapatan Asli Daerah (PAD), Dana Transfer Ke Daerah Dan Belanja Modal Terhadap Kemandirian Keuangan Daerah Pada Kabupaten/Kota Di Sumatera Periode2020-2024 - Farizs Gilang Alfaridzy; Indrayeni . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD), Intergovernmental Transfers, and Capital Expenditure on Regional Financial Independence in regencies and cities across Sumatra Island during the period 2020–2024. This research adopts a quantitative approach using a causal associative method. The population consists of all regency and city governments in Sumatra Island totaling 154 regions, and a saturated sampling technique was applied so that the entire population was used as the research sample. The data used are secondary data obtained from Regional Budget Realization Reports published by the Directorate General of Fiscal Balance (DJPK). Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that Regional Original Revenue (PAD) has a positive and significant effect on regional financial independence. In contrast, Intergovernmental Transfers and Capital Expenditure have a negative and significant effect on regional financial independence. These findings suggest that increasing PAD can strengthen regional fiscal independence, while high dependence on transfer funds and increases in capital expenditure in the short term have not yet contributed to improving regional financial independence. Therefore, local governments need to optimize regional revenue sources and manage fiscal resources more effectively to enhance sustainable regional financial independence.